TRICHINELLA SPECIES AND TOXOPLASMA GONDII IN WOLVERINE (GULO GULO) FROM NORTHWESTERN CANADA - Sharma, Rajnish (2019)
Trichinella spp. and Toxoplasma gondii are important foodborne parasites world-wide, and are especially important in wildlife harvested for food and fur in Canada. Due to their top position in the food web as well as their scavenging behavior, large carnivores such as wolverines may be more exposed to these parasites through foodborne routes. Limited information is available on these parasites in wildlife from northwestern Canada, and such information is critical to control and prevent infections in animals and people. To conduct surveillance studies, the first and foremost step is to select samples suitable for detection of the parasites. I first compared tongues and diaphragms of wolverine harvested for fur for the detection of Trichinella species (Chapter 2), and found tongue could act as a better sampling site; therefore, further epidemiological studies on Trichinella used tongue tissues (Chapter 3). Using a double separatory funnel digestion method, we found larvae of Trichinella in the tongue of 78% (95% CI = 73–82) of 338 wolverine from the Yukon Territory. The mean intensity of infection was 22.6 ± 39 (SD, range 0.1–295) larvae per gram of muscle tissue. Species or genotypes of Trichinella circulating in the wildlife of the Yukon are not known. Using multiplex PCR, Trichinella T6 was revealed as the predominant genotype (76%), followed by T. nativa (8%); mixed infections with Trichinella T6 and T. nativa (12%) were observed. While confirming multiplex genotyping by DNA sequencing, I unexpectedly discovered a previously undescribed species of Trichinella in a wolverine from the Canadian North that appeared identical to T. nativa in multiplex PCR. Therefore, I investigated the phylogeny, geography and host range of this undescribed species in Chapter 4. My findings showed that this unknown species of Trichinella, to be designated initially as the T13 genotype, is in fact ancient, and putative sister of the lineages including T. patagoniensis and the remaining species [(sister-clade (T1 + T7) and ...